Characterizing fermentable carbohydrate foods in the diets of children with abdominal pain-related disorders of gut-brain interaction and healthy children - Vishnu Narayana; Jocelyn Chang; Ann R. McMeans; Tasha Murphy; Rona L. Levy; Robert J. Shulman; Bruno P. Chumpitazi (PLoS ONE, 2025)
Objectives Restricting dietary fermentable oligosaccharides, disaccharides, monosaccharides, and polyols (FODMAPs) can alleviate symptoms in children with disorders of gut-brain interaction (DGBI). Due to the restrictions of a low FODMAP diet (LFD), a less restrictive FODMAP Gentle diet (FGD) has been suggested. However, the types and amounts of high FODMAP foods and carbohydrates commonly consumed by children have not been studied. We aimed to identify the high FODMAP foods and proportions of FODMAP carbohydrates consumed by children with DGBI and healthy children (HC) and to determine which usually ingested FODMAPs would be restricted on the FGD. Methods Three-day diet records from both children with DGBI and HC were analyzed and compared to assess the type and amount of high FODMAP foods and carbohydrates ingested. Additionally, the ingested FODMAPs that would be restricted on the FGD were determined. Results Diet records from 77 children with DGBI and 64 HC were analyzed. The number of foods ingested daily was similar between children with DGBI and HC (12.3 ± 4.2 vs 12.9 ± 3.4, respectively); high FODMAP foods comprised most foods eaten in both groups. Children with DGBI (vs. HC) ate fewer high FODMAP foods per day (6.5 ± 2.3 vs 8.7 ± 2.4, P < 0.0001, respectively). Fructans were the most consumed FODMAP carbohydrate in both groups, and children with DGBI (vs. HC) consumed fewer fructans, lactose, fructose, and polyols (all P < 0.0001). The top 3 food categories consumed in both groups were wheat-containing foods, dairy, and fruits/ 100% fruit juices. In children with DGBI, 80.9% of the high FODMAP foods consumed would be limited on the FGD. Conclusions Children with DGBI consume fewer high FODMAP foods and carbohydrates than HC, with the top consumed FODMAP carbohydrates being fructans, lactose, and fructose. A FGD would restrict most high FODMAP foods consumed by children with DGBI.